2021
DOI: 10.1371/journal.pone.0256125
|View full text |Cite
|
Sign up to set email alerts
|

Association of mental health help-seeking with mental health-related knowledge and stigma in Japan Rugby Top League players

Abstract: Background Globally increasing clinical and research interests are driving a movement to promote understanding and practice of mental health in elite athletes. However, few studies have yet addressed this issue. This study aims to describe the association of the intention to seek help with mental health knowledge and stigma and the severity of depressive symptoms in Japan Rugby Top League players. Methods As a target population, we studied 233 Japan Rugby Top League male players (25–29 years = 123 [52.8%]), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Based on this position, elite athletes are more likely to miss opportunities to talk about their mental ill health inside and outside the team and may become isolated if they have mental healthcare needs. Our previous research has shown that even elite athletes with greater mental health knowledge may feel unable to seek help when they experience poor mental health status 26. It is necessary to create a psychologically safe environment inside and outside of the team so that athletes can talk about themselves, including their mental health concerns 24 27…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this position, elite athletes are more likely to miss opportunities to talk about their mental ill health inside and outside the team and may become isolated if they have mental healthcare needs. Our previous research has shown that even elite athletes with greater mental health knowledge may feel unable to seek help when they experience poor mental health status 26. It is necessary to create a psychologically safe environment inside and outside of the team so that athletes can talk about themselves, including their mental health concerns 24 27…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research has shown that even elite athletes with greater mental health knowledge may feel unable to seek help when they experience poor mental health status. 26 It is necessary to create a psychologically safe environment inside and outside of the team so that athletes can talk about themselves, including their mental health concerns. 24 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Coaches may neglect treatment because of the common misperception that help-seeking is incongruous with the ideals of stoicism and mental toughness—misunderstood values that are commonly promoted and glorified in elite sport. 76 , 77 To better support coaches, sporting organizations, federations, and governing bodies need to nurture high-performance cultures that destigmatize mental ill health and reposition help-seeking. Future research might examine the relationship between mental health and coaching effectiveness to leverage proponents of positive psychology, and evaluate whether performance could be employed as a “hook” to engage elite-level coaches with mental health practices and help-seeking.…”
Section: Early Intervention For Mental Health In Elite-level Coachesmentioning
confidence: 99%
“…The next step is expected to be developing a systematic care system linked to epidemiological research findings. As one of the limited epidemiological findings of the Japanese sports context, particularly in the top-category or professional level, our team collaborated with the JRPA and reported on the prevalence and factors related to mental health symptoms in elite athletes [5, 6, 23]. Following these reports, several epidemiological findings about mental health symptoms in highly competitive sports settings have been published [24, 25].…”
Section: Introductionmentioning
confidence: 99%